Impact of Abiotic Factors on the Incidence of Brown Plant Hopper Nilaparvata lugens Stal in Rice Crop at Cuddalore District, Tamil Nadu, India - D, Prakash; Asaf, Chand (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Rice is a dietary staple of more than half of world’s population, and more than 90% of world’s rice is grown and consumed in Asia alone but faces significant threat from insect pests most importantly Brown plant hopper (BPH), Nilaparvata lugens Stal, consider to be a major insect pest of rice. This study showcases the correlation between weather parameters and BPH infestation in rice crop grown in two Kharif (rainy) and two Rabi (winter) seasons of 2022 and 2023 in Chidambaram, Tamil Nadu, India. Non-resistant rice varieties (ADT 43 and ADT 54) were used. BPH population and weather data (maximum and minimum temperature, relative humidity, sunshine hours, rainfall, and wind speed) were collected weekly. In all the seasons the BPH population ranged from 0.0 to 8.2 at its peak in our study area. Results showed that BPH populations were higher during kharif seasons compared to rabi seasons. Maximum temperature and sunshine hours exhibited a positive correlation with BPH population, while rainfall and minimum temperature were negatively correlated. By taking into account these weather parameters, farmers can predict and monitor fluctuations in pest populations. This enables them to apply pesticides strategically, only when economically justified, and to implement a range of integrated pest management techniques.